Comparison of Hemodynamic Support by Impella vs. Peripheral Extra-Corporeal Membrane Oxygenation: A Porcine Model of Acute Myocardial Infarction - Nix, Christoph; Ishikawa, Kiyotake; Meyns, Bart; Yasuda, Shota; Adriaenssens, Tom; Barth, Svenja; Zayat, Rashad; Leprince, Pascal; Lebreton, Guillaume (Frontiers in Cardiovascular Medicine, 2020)
Objectives Several mechanical circulatory assist devices are used to treat critically ill patients requiring hemodynamic support during post-myocardial infarction or cardiogenic shock. However, little guidance is available to choose an appropriate device to match a particular patient’s needs. An increased understanding of hemodynamic effects of the pump systems and their impact on myocardial pre-/afterload might help to better understand their behavior in different clinical settings. Methods This was an open-labeled, randomized acute animal experiment. A model of acute univentricular myocardial injury by temporary balloon occlusion was used. The experiment was carried out in 10 juvenile female Piétrain pigs. The animals were randomized to mechanical hemodynamic support either by peripheral veno-arterial (VA-)ECMO or Impella CP. Results While both devices were able to provide flows above 3 L/min and maintain sufficient end-organ perfusion, support by Impella resulted in a significantly more pronounced immediate effect on myocardial unloading: At the onset of device support, the remaining native cardiac output was reduced by 23.5±15.3% (ECMO) vs 66.2±36.2% (Impella, p=0.021). Native stroke volume was significantly decreased by Impella support compared to ECMO, indicating less mechanical work being conducted by the Impella-supported hearts despite similar total assisted cardiac output. Conclusions Peripheral VA-ECMO and the transaortic Impella pump resulted in contrasting hemodynamic fingerprints. Both devices provided sufficient hemodynamic support and reduce left ventricular end-diastolic pressure in the acute setting. Treatment with the Impella device resulted in a more effective volume unloading of the left ventricle. A significant reduction in myocardial oxygen consumption equivalent was achieved by both devices: The Impella device resulted in a left-shift of the pressure-volume loop and a decreased pressure-volume-area (PVA), while VA-ECMO increased PVA but decreased heart rate. These data highlight the importance of specifically targeting heart rate in the management of AMI patients on hemodynamic support.